Study of Fiqh Aulawiyat on Celibacy and Childfree in the Reality of Social Life - Nahdhiyyah, Husnun (Jurnal Al-Qadau: Peradilan dan Hukum Keluarga Islam, 2024)
Celibacy or in Arabic is called tabattul (being celibate forever) is defined as a person's attitude not to commit themselves to a sexual relationship, while Childfree is a person's decision not to have children in their life for certain reasons. If someone is faced with a case that allows childfree and celibacy, which is the main thing in the jurisprudence of aulawiyyat. The method used in this research is library research or what is usually called Library Research with a comparative approach. The research results show that the study of Fiqh Aulawwiyat can prioritize childfree over celibacy because one of the impacts of celibacy can be eliminated by implementing the sunnah of the Prophet Muhammad SAW, namely marriage. However, prioritizing childfree over celibacy does not mean that the author fully supports the practice of childfree, but it is better to avoid both problems and prioritize legal marriage and living out one's nature as a human being.